Writing with the sea: reflections on in/experienced encounters with ocean space. (October 2017) - Peters, Kimberley; Brown, Mike
How does being with the sea change how we write about the sea? This article is constructed as a reflective/reflexive consideration of being at sea as part of an experimental week-long symposium held on board an 80-foot yacht in the Hauraki Gulf, New Zealand, in early 2016. The event focused on the ways society lives with the sea in the 21st century – how awareness is raised and action is instigated – in light of growing threats to ocean spaces worldwide. While generating conversation on this theme, the location of the symposium was also pivotal in generating embodied knowledge of the topic under investigation. This article follows the afterthoughts of the symposium organiser (an outdoor educator and professional yacht skipper) and an attendee (a geographer of the sea, non-swimmer and first-time sailor). It investigates how academic events that take place in place – in this case at sea – may generate unique knowledge on conference themes, and for academic work more generally, by opening up new experiential worlds.